Pemilu Legislatif DKI Jakarta dalam Paparan Media Daring: Analisis Isi Pemberitaan Caleg Dapil I,II,dan III Jakarta pada Pemilu 2019 - Titin Setiawati (Program Studi Ilmu Komunikasi, 2019)
After the Reformation era, started in 2014, the system for general elections was changed by open proportional system. The legislative candidates with the most votes will be elected as members of parliament, and for the second time the system was repeated in April 2019. In media sector, online media utilization has gained widespread attention during the last election. Online media is often used for election campaigns; especially by parties and candidates who have an interest in voting for the constituents. This research using the media monitoring method for online media from January to February 2019 for Jakarta I, II, and III Election Areas. The results of the study show that the news shows more political events in general. Most of the news is not directed at parties or candidates so it is less effective in introducing parties and candidates. News in online media is also less capable of being a positive learning tool for politics for the communityKeyword : content analysis, online media, election, parliament election